Ethics - Thompson, Mel (Hodder education, 2006)
Teach Yourself Philosophy of Religion New Edition is the essential guide for anyone wanting to investigate religion in the context of philosophy. It explores the key principles upon which religion is based and considers how religion relates to our understanding of life. It answers questions such as: how do religious beliefs relate to morality? should religions be judged according to the behaviour of their followers? is it necessary to be committed to a religion or are religious questions and experiences open to all? This new edition has been fully updated so that it addresses current issues and questions. Topics discussed include: religion in education and in politics, the evolution debate, terrorism carried out in the name of religion, religion and psychology and religion in a largely secular society.